2014
DOI: 10.1099/ijs.0.063750-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Symbiobacterium ostreiconchae sp. nov., Symbiobacterium turbinis sp. nov. and Symbiobacterium terraclitae sp. nov., isolated from shellfish, emended description of the genus Symbiobacterium and proposal of Symbiobacteriaceae fam. nov.

Abstract: Three novel moderately anaerobic, thermophilic, rod-shaped bacterial strains, KY38T, KY46T and KA13T, were isolated from shellfish collected on the Pacific coastline of Enoshima, Japan. Phylogenetic analysis of the 16S rRNA gene sequences indicated that these bacteria belong to the genus Symbiobacterium , sharing sequence similarities of 97.8 % (KY38T), 96.4 % (KY46T) and 93.3 % (KA13T) with the type strain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…4 and Additional file 1 : Figure S6). Members of this family have been detected in paddy soils [ 51 ] and shown to be capable of producing propionate [ 52 ]. Most likely, Peptococcaceae were the major players in syntrophic propionate oxidation (Additional file 1 : Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…4 and Additional file 1 : Figure S6). Members of this family have been detected in paddy soils [ 51 ] and shown to be capable of producing propionate [ 52 ]. Most likely, Peptococcaceae were the major players in syntrophic propionate oxidation (Additional file 1 : Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…According to Da Costa et al (2009), the genera Thermaerobacter and Sulfobacillus are classified within the family XVII Incertae Sedis within the class Clostridia . The genus Symbiobacterium is placed in the family XVIII Incertae Sedis within the same class, but the family Symbiobacteriaceae was recently proposed (Beppu & Ueda, 2009; Shiratori-Takano et al , 2014). 16S rRNA gene phylogeny showed that the genus Symbiobacterium is related to the phylum ‘ Actinobacteria ’ rather than members of the phylum Firmicutes (Ohno et al , 2000; Ludwig et al , 2009b), but relatedness among the class Clostridia was also shown by genome-based analyses (Ueda et al , 2004; Nishida et al , 2009).…”
mentioning
confidence: 99%
“…An isomer of fumaric acid is maleic acid, which is copolymerized with acrylic acid to form the side chains of the inhibitor. Representatives of Symbiobacterium reduce nitrate (Shiratori-Takano et al, 2014), however the genus identified in the batch experiments is only distantly related to Symbiobacterium (identity 85 %-87 %). Relatives of Thermincola were represented by up to 10 %.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 98%
“…The scaling inhibitor NC47.1 B is a comb polymer with polycarboxylate side chains. It prevents the formation of crystal nuclei mainly via a threshold effect (Sieben and Niederrhein Chemie GmbH, 2016). The spine structure consists of a polysaccharide, which makes the molecule accessible for biodegradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation